Pendapat Tokoh Agama Terhadap Pelaksanaan Perkawinan Wanita Hamil (di Kantor Urusan Agama Kecamatan Katingan Hilir) - Anwar, Arif; Zabidi, Haya; Muhammad, Muhammad (Sharia Journal and Education Center Publishing, 2026)
This research is motivated by the problem of promiscuity among young people which often leads to unwanted things, namely the occurrence of pregnancy before marriage. The phenomenon of pregnancy outside of marriage is a fairly sensitive issue in various societies, not only regarding reproductive health aspects, but also has a wide impact on social, cultural, psychological, and legal aspects. In the midst of globalization and information disclosure, this phenomenon is increasingly complex, and its handling requires a holistic approach and empathy from all parties. This type of research is qualitative by going directly into the field to conduct interviews. Using a normative and juridical approach. Using primary data obtained from the views of religious leaders on the marriage of pregnant women out of wedlock and the status of children from the marriage of pregnant women. The results of the study show, first, that the factor of pregnant women's marriage is due to low levels of faith, too free association, lack of supervision from parents, low Islamic law education, and lack of legal awareness from the community and the perpetrators. The second result is about the opinion of religious leaders on the marriage of pregnant women out of wedlock, namely that pregnant women out of wedlock can be married to men who impregnate her, can be carried out without waiting for the birth of their child, marriage takes place when the woman is pregnant, there is no need for remarriage after the child conceived is born.